The relevance of "born global" definition in the research process - Irena Vaivode; Deniss Sceulovs (Trends Economics and Management, 2019)
Purpose of the article: The purpose is to create a new definition of a Born Global (BG) company, more relevant to contemporary global business situation. BG companies are the phenomenon which contributes to national economic development by fostering innovation, creating stocks of skills and knowledge, supporting industrial growth. It would be a right decision to study the options to develop BG companies in Latvia, as a small number of exportcapable sectors represent a factor that renders the Latvian economy sensitive to any changes in the external environment. Developing standard definitions helps to increase the research clarity as well as the comparability of firms across regions, countries and specific industries. Methodology/methods: The research is conducted through literature reviews, case studies, survey studies, and modelling. The focus group discussion was organized to clarify the standard definition of the BG with the aim of using this definition as a basis for further research. Scientific aim: The newly created definition of born global companies is based on scientific justification for all the features it contains. The authors would like to base the justification on the causation and effectuation theories which include all the features associated with orientation to revenues and international market capacity. Findings: The authors highlight the role of defining and predicting of the opportunities for a company to become a BG. The theories help to justify an inclusion of all the corresponding components in the definition. This theoretical justification could serve as the basis for the further investigation of the relationship between effectual conditions and the outcome (potential to be a born global company). Conclusions: Before studying the options to develop BG companies as the growth patterns in Latvia, it is necessary to find the most appropriate definition of the BG. The newly created definition is justified by causation and effectuation theories.
Keywords: F23; F62; H50; M21; 650; born-global company; business environment; entrepreneur; globalization; internationalization; national economy